Construction of the image of Ermak in late XVI – XVII centuries: official, church and folk practices - S. A. Chernyshov (Омский научный вестник: Серия "Общество. История. Современность")
The article examines the evolution of ideas about Ermak from the end of the 16th and throughout the 17th centuries, identifies the main subjects of constructing his image. The aim of the study is to systematize and factorial analysis of the evolving discourses about Ermak’s campaign in the initial period of constructing images and legitimizing the annexation of Siberia to the Russian state in internal communicative practices. The research is carried out on the basis of the analysis of chronicles, act and diplomatic materials, materials of historical and ethnographic research. The article is the first to review the evolution of Ermak’s image in various communication practices, not in the context of the search for «historical truth», but to analyze the factors of such evolution and the formation of the internal logic of coexistence in one image of several contradictory characteristics. This study shows how, as a result of collective action on the construction of «Ermak» by various subjects of communication (government, church, Stroganovs, folk art), a contradictory but universal image of a hero has come down to us, suitable for any communication task — from justifying «Cossack freemen» to evidence of the «state» nature of the campaign to Siberia.